2021
DOI: 10.1155/2021/8868361
|View full text |Cite
|
Sign up to set email alerts
|

P2X7 Receptor Induces Pyroptotic Inflammation and Cartilage Degradation in Osteoarthritis via NF‐κB/NLRP3 Crosstalk

Abstract: Osteoarthritis (OA) is an urgent public health problem; however, the underlying causal mechanisms remain unclear, especially in terms of inflammatory mediators in cartilage degradation and chondrocyte imbalance. P2X7 receptor (P2X7R) is a critical inflammation switch, but few studies have examined its function and mechanisms in OA-like pyroptotic inflammation of chondrocytes. In this study, Sprague–Dawley rats were injected in the knee with monosodium iodoacetate (MIA) to induce OA, followed by multiple intra-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
67
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 99 publications
(70 citation statements)
references
References 38 publications
3
67
0
Order By: Relevance
“…CY-09 reduced bone loss in osteoarthritis modeling. However, the route of administration is achieved by intra-articular injection in the knee ( 62 ). At present, the research on OLT1177 in OP has not been reported.…”
Section: Potential Therapeutic Target Of Nlrp3 Inflammasome In Opmentioning
confidence: 99%
“…CY-09 reduced bone loss in osteoarthritis modeling. However, the route of administration is achieved by intra-articular injection in the knee ( 62 ). At present, the research on OLT1177 in OP has not been reported.…”
Section: Potential Therapeutic Target Of Nlrp3 Inflammasome In Opmentioning
confidence: 99%
“…It has been previously reported that the selective activator Bz-ATP increases P2X7 expression and induces the OA phenotype in primary chondrocytes (Li et al, 2021b). The results of animal experiments (Figures 1, 2) showed that changes in the expression level of P2X7 regulate autophagy and apoptosis in chondrocytes.…”
Section: Moderate and Excessive P2x7 Activation Has Opposing Effects On Mtor And Autophagy And Both Induce Er Stressmentioning
confidence: 69%
“…We previously reported (Zhang et al, 2019;Li et al, 2021b) that P2X7 expression was increased in the rat OA model. Furthermore, we observed that treadmill exercises effectively alleviated OA occurrence and development.…”
Section: Treadmill Exercise Increases P2x7 Expression Activates Early Stage Autophagy and Induces Er Stress-mediated Apoptosis During Oamentioning
confidence: 93%
See 2 more Smart Citations